(untitled) (Bodhi Path, 2022)
There is no doubt that followed by the attainment of Perfect and Complete Buddhahood, Gautama the Buddha, turned the Wheels of Dharma at various places for the sake of welfare of sentient beings. Although initially He remained silent for seven weeks without expressing any word, but later at the request of Brahmā, He decided to bring welfare through showing them the right path to liberation. Being a matchless and skillful Guide, He never tried to attract and establish His disciples to path by means of His miraculous power by saying ‘Tathāstu (So be it)!. Instead, He just introduced and showed the right path according to the wish, temperament and capacity of His disciples.